Sustainable Entrepreneurship in Patchouli Cultivation: a Conceptual Framework - Harifuddin Thahir; Suryadi Hadi; Femilia Zahra; Irdinal Arief; Elimawaty Rombe; Roy Irawan Mendi (UPT Penerbitan Universitas Jember, 2021)
The world’s demand of essential oil has been increased and could contribute to increase the benefits for several countries. Indonesia has potential for patchouli farm and is one of largest exporter countries. Patchouli is one of the sources of essential oil has contributed to fill the high demand. Farmers has the key role in patchouli cultivation must sustain their production without harm the ecosystem. This study aims to identify the theory, experience and perspective of sustainable entrepreneurship in the agribusiness sector, namely patchouli cultivation. This study reviewed previous research on several data bases, including: Google Scholar and Researchgate. Several articles related to research topics from reputable journals were collected. The results of this study were carried out succeeded in formulating a research model on the influence of sustainable attitudes, sustainable norms, sustainable behavior, achievement of opportunities, three points of sustainability, on sustainable entrepreneurship. The research model that was formed is recommended for further research. This conceptual paper formulates a model and requires empirical research to generalize the existence of the theory in the future. The research model formulated in this study is still relatively new in the field of sustainable entrepreneurship in patchouli cultivation. Keywords: Sustainable, Entrepreneurship, Patchouli, Conceptual Framework.